Hymenolepis dimunata Infection in a Child of 14 month - Thakur, NK; Mishra, SK; Neupane, GP; Jha, A (Journal of Nepal Health Research Council, 2009)
We report a case, a 14 month old male child who presented with fever and diarrhea for a month. It was diagnosed as a case of H dimunata infection, which is a sole parasite of rat. Very few cases of such infection have been reported in Nepal. The treatment is done with either Niclosamide or Praziquantel, but the main concern is about the diagnosis of the condition. Since, H dimunata is a sole rat parasite, it is hardly ever thought about a cause of the diarrhea. Key words: Diarrhea, H dimunata, Niclosamide   DOI: 10.3126/jnhrc.v7i1.2294 Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 49-51